Twins excited to get new sets of school items - UMP, PNC (2019)
Two pairs of twins were simply excited to start schooling again after receiving new sets of school items given to them during the ‘Back-To-School’ programme, ‘Give Them Our Heart, Give Them Happiness’ recently.